Trends and inequalities in (healthy) life expectancy by neighbourhood during the COVID-19 epidemic in Barcelona - Xavier Bartoll-Roca; Laia Palència; María Jesús Calvo; Katherine Pérez (Gaceta Sanitaria, 2023)
Objective: To analyse the trend in life expectancy (LE), healthy life expectancy (HLE) and socio-economic inequalities by neighbourhood in Barcelona from the pre-pandemic period (2018-2019) to the pandemic period (2020-2021). Method: LE and HLE at birth were computed using the municipal register of inhabitants and quality of life (EuroQol) from the Barcelona Health Survey of 2016. Inequalities were assessed with the gap between quantiles of neighbourhood income. Results: In 2020, there was a reduction in LE among men (−1.98 years) and women (−2.44) and in HLE among men (−1.44). Socio-economic inequalities in LE and HLE between neighbourhoods widened since 2019 to 2021 (LE: from 3.92 to 4.86 years for men, and from 1.30 to 3.60 for women; HLE: from 6.88 to 7.70 years for men, and from 7.85 to 9.31 for women). Conclusions: The pandemic has substantially reduced LE and HLE, with larger effects among low-income neighbourhoods, especially among women. Resumen: Objetivo: Analizar la evolución de la esperanza de vida (EV), la esperanza de vida en buena salud (EVBS) y las desigualdades socioeconómicas por barrios en Barcelona desde el periodo prepandémico (2018-2019) hasta el periodo de pandemia (2020-2021). Método: Se calcularon la EV y la EVBS al nacimiento utilizando el registro municipal de habitantes y la calidad de vida (EuroQol) de la Encuesta de Salud de Barcelona de 2016. Las desigualdades se valoraron mediante la brecha entre los cuantiles de ingreso por barrios. Resultados: En 2020 hubo una reducción en la EV en los hombres (−1,98 años) y las mujeres (−2,44), y en la EVBS en los hombres (−1,44). Las desigualdades socioeconómicas en EV y EVBS por barrios se ampliaron de 2019 a 2021 (EV: de 3,92 hasta 4,86 años en hombres y de 1,30 hasta 3,60 años en mujeres; EVBS: de 6,88 hasta 7,70 años en hombres y de 7,85 hasta 9,31 años en mujeres). Conclusiones: La pandemia ha reducido sustancialmente la EV y la EVBS, con mayores efectos en los barrios de menor renta, en especial en las mujeres.